2014
DOI: 10.1186/1471-2334-14-394
|View full text |Cite
|
Sign up to set email alerts
|

Legionella control in the water system of antiquated hospital buildings by shock and continuous hyperchlorination: 5 years experience

Abstract: BackgroundTo control the presence of Legionella in an old hospital water system, an integrated strategy of water disinfection-filtration was implemented in the university hospital Umberto I in Rome.MethodsDue to antiquated buildings, hospital water system design and hospital extension (38 buildings), shock hyperchlorination (sodium hypochlorite, 20–50 ppm of free chlorine at distal points for 1–2 h) followed by continuous hyperchlorination (0.5-1.0 mg/L at distal points) were adopted, and microbiological and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 20 publications
2
23
0
5
Order By: Relevance
“…Different factors are required to be studied when selecting the most suitable water disinfection method in health care facilities in order to guarantee water quality (Zhang et al 2007). No method can guarantee absolute total disinfection and when colonization occurs, it is extremely difficult to eliminate it (Scaturro et al 2007;Lin, Stout, and Yu 2011;Cristino, Legnani, and Leoni 2012;Orsi et al 2014). Chlorine (Cl) is widely used as a disinfectant in Portuguese water systems (Diegues 2013) and it is considered efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Different factors are required to be studied when selecting the most suitable water disinfection method in health care facilities in order to guarantee water quality (Zhang et al 2007). No method can guarantee absolute total disinfection and when colonization occurs, it is extremely difficult to eliminate it (Scaturro et al 2007;Lin, Stout, and Yu 2011;Cristino, Legnani, and Leoni 2012;Orsi et al 2014). Chlorine (Cl) is widely used as a disinfectant in Portuguese water systems (Diegues 2013) and it is considered efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Although the technique represents the decisive treatment for bacteria control and elimination in most w ater systems most especially in old w ater distribution netw orks (Schoenen, 2002;Orsi et al, 2014), Legionella is reported to be more tolerant to chlorine than other bacteria including Escherichia coli (World Health Organization (WHO), 2007). Evidence of the presence of biofilm is reported to be a key element in its ability to offer such resistance.…”
Section: Characterization Of Efficacy Advantages and Disadvantagesmentioning
confidence: 99%
“…Although the use of chlorine eliminates w ater odour (Wajon et al, 1988), w ater quality is reduced (organoleptic and chemical) often, as a result of chlorine levels (>0.5 < 1.0 mg/L) (Orsi et al, 2014). In terms of health, an increased risk of bladder cancer also appears to be associated w ith the consumption of chlorinated w ater (Cantor, 1997) along w ith other illnesses such as asthma and dermatitis w hich have also been reported (Gorchev and Ozolins, 2011;Faw ell, 2003).…”
Section: Effect Of Hyper Chlorination On W Ater Quality and Its Applimentioning
confidence: 99%
“…10,11 Certain environmental conditions are recognized as increasing the risk from L pneumophila in water systems by either permitting higher levels of growth or creating an infectious aerosol. 12 These include temperatures between 20°C and 45°C, storing water, and the presence of organic and inorganic material in the system. The "traditional" regimen for controlling L pneumophila is based on temperature control, keeping cold water <20°C and hot water stored at least at 60°C, distributed so that it reaches 55°C at outlets within 1 minute.…”
mentioning
confidence: 99%